(untitled) - Ellis, Claire (Portland, Or., 2001)
A look at the customs, etiquette, culture and traditions of Vietnam for those visiting the country. A new title from the CULTURE SHOCK! series
Giao tiếp liên văn hóa
Keywords: National characteristics, Vietnamese,Đặc điểm quốc gia, Việt Nam